Portable Filtration with Solar Photovoltaic-Powered IoT-Based Water Quality Monitoring System for Aquaponics - Nasri, Dzul Idham; Mohammad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2023)
This paper introduces a solar-powered portable filtration system and an Internet of Things (IoT) based water quality monitoring setup to elevate traditional aquaponics into intelligent ecosystems. The filtration scheme addresses noxious elements like ammonia, pH fluctuations, and particulate pollutants that can harm fish and plants. It employs a three-stage process encompassing radial flow, mechanical, and biological filters. Yet, the maintenance demands of the mechanical filter led to the creation of a portable substitute. Simultaneously, an IoT water quality monitoring system is indispensable for real-time assessment of parameters like dissolved oxygen, pH, total dissolved solids, turbidity, and temperature. Notably, the portable filtration system demonstrates substantial efficacy, correcting pH levels from 6.07 to 7.21, reducing concentrations from 105 ppm to 70 ppm, and ameliorating water clarity. Calibration of IoT sensors highlights precise temperature measurements (±0.5°C), accurate total dissolved solids (TDS) readings for both soap water (13000 ppm) and plain water (77 ppm), and well-aligned turbidity measurements for varying water densities. The system design emphasizes user-friendliness, cost-efficiency, and sustained effectiveness, rendering it versatile for diverse agricultural and aquacultural applications. By combining solar energy and IoT technology, this innovation enhances control, sustainability, and the overall vitality of aquaponic environments. The solar-powered PonicsMon prototype showcases a viable battery charging duration of approximately 17.28 hours, solidifying its practicality.